Relation between Body Iron Store and Insulin Resistance in Type 2 Diabetes - Wafa F. AL-Tai; Inaam A. Mohammed; Mayada S. Sabri (مجلة بغداد للعلوم)
The clinical impact of interaction between body iron status (serum iron and ferritin ) and type 2  diabetes  has been investigated in this study . Thirty six females were enrolled, eighteen type 2 diabetes and eighteen apparently healthy. These two groups were matched for age and body mass index BMI. The eighteen diabetes females were matched for age, BMI, pharmacological treatment (oral hypoglycemic agent), and chronic diabetes complications .